Ion exchange study of carbonate, nitrate and dioctyl sulfosuccinate with anthraquinone-2-sulphonate encapsulated in inorganic layered structures - Yahaya, Asmah Hj; Bin Hussein, Mohd Zobir; Seh, Wong Song (Elsevier, 2003)
Layered organic-inorganic hybrid composite of anthraquinone 2-sulfonate (AQ2) with Zn-Al layered double hydroxide (LDH) was prepared and its ion exchange was examined with carbonate, nitrate and dioctyl sulfosuccinate (DSS) in aqueous environment at various concentrations of the sodium salt solutions, 0.05, 0.1 and 0.2 M, at room temperature. The ion exchange procedure produced an LDH or another material of which basal spacing was shrinked or expanded from 19 to 7.4, 23.4 to 24.4 and 19.1 to 19.5 Å for carbonate, DSS and nitrate ion exchanged, respectively, depending on the concentration. This is due to the size and the orientation of the anions, which is accommodated in the LDH inorganic layered structure. Ion exchange was found to be completed for carbonate and DSS. However, no ion exchange can be observed for nitrate. This indicates that carbonate and DSS have a higher affinity than AQ2 to be intercalated into the inorganic layered structure. On the other hand, nitrate has a lower affinity than AQ2. Therefore, the affinity of the anion shows the trend: CO32- ≳ DSS > AQ2 > NO3- under our experimental conditions.